Smoke visualization under heat transfer by free convection on horizontal cylinder surface - Неїло, Роман Володимирович (Technology audit and production reserves, 2014)
The method of visualizing a dynamic field in conditions of free convection by introducing a laminar smoke stream into the area which is vertically lower than the existing thermal and dynamic boundary layers has been proposed and examined in the paper. The suggested method is simple, obvious, cheap and fast enough, that allows advising it for applying in the study of free-convective heat transfer problems using air as a heat-transfer agent. As a result of the conducted research, a set of assumptions, giving the basis to calculations and methods of analyzing experiment results has been demonstrated. In particular, among them there can be singled out the following: the laminarity of a heat-transfer agent motion mode, the laminarity of a thermal tracing and boundaries of its sustainable occurrence over a hot surface, the growth of boundary layer thickness in the cylinder stern, symmetry of washing cylinders from different sides from the vertical plane of symmetry, and others. Juxtaposing the results with the data, represented in the literature, shows a high correspondence.